Persistent proteinuria as an indicator of renal disease in HIV-infected children - Yuni Hisbiiyah; Risky Vitria Prasetyo; Dwiyanti Puspitasari; Ninik Asmaningsih Soemyarso; Ismoedijanto Moedjito; Mohammad Sjaifullah Noer (Indonesian Pediatric Society, 2016)
Background Persistent proteinuria (microalbuminuria) has been reported to be a precursor of HIV-related renal disease. Screening allows for early management in order to prevent the progression of renal disease and decrease morbidity and mortality associated with chronic kidney disease in HIV. Several studies have been done on renal manifestation in HIV-infected children from American and African regions, but similar studies from Asia are lacking.Objective To determine the prevalence of persistent proteinuria in HIV-positive children on antiretroviral therapy (ARV) in Dr. Soetomo Hospital, Surabaya.Methods A cross-sectional study on children with HIV and treated with Â highly active antiretroviral therapy (HARRT) was done from August 2014 to February 2015. Microalbuminuria was measured by the ratio of urine albumin to creatinine (ACR), while proteinuria was measured by dipstick. Measurements were performed 3 times in 4-8 weeks. All subjects underwent complete evaluation of blood tests, serum creatinine, blood urea nitrogen (BUN), CD4 counts, and urinalysis. Data were analyzed using Chi-square and logistic regression tests.Results Of 38 children on HARRT enrolled in this study, 2 subjects developed acute kidney injury (AKI), 4 subjects were suspected to have urinary tract infection (UTI), and 1 subject was suspected to have urinary tract stones. The prevalence of persistent microalbuminuria was 2.6%. There was no correlation between immunological status, WHO clinical stage, or duration of ARV and the incidence of persistent proteinuria (P>0.05).Conclusion The prevalence of persistent proteinuria is Â lower in younger HIV-infected children at a non-advanced stage and HIV-infected children with normal immunological status who are on HAART. We provide baseline data on the renal conditions of HIV-infected children in the era of HAART, before tenovofir is Â increasingly used as an antiretroviral therapy regimen in Indonesia.